Transmission of Impact Vibration on Concrete and Mortar Sheets - Carlos Morón; Alfonso García; Daniel Ferrández; Víctor Blanco (Shock and Vibration)
The present work exposes an alternative system for detecting vibrations generated by impact on concrete and mortar sheets. In order to carry out the tests it is necessary to implement a system of measurement different than the one proposed by the current UNE EN 140-7. This system consists of an amplifier and a striking device that is also able to measure the deformation of the material once the impact has been produced. This system is able to detect variations in transmission of vibration at the same frequency between the various building materials employed, after establishing a relationship between the theoretical predictions and the experimental results. Thus, this system could be used as a vibration detection system and as an alternative method of standardization of materials against their acoustic characteristics.